Pengembangan Sistem Konversi Citra ke G-Code untuk Aplikasi Manufaktur - Retno Tri Wahyuni; Djoko Purwanto; Tri Arief Sardjono (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
Along with the development of technology, has provided software image converter with bmp format into G-code. But the software is not yet integrated with the camera. Software development about Image to G-code converter integrated with camera present in this paper. Before the G-code file is created, set the parameter like x-y resolution for image resolution, carving dimension and maximum depth.Object with varying shapes and size used in testing process. G-code file run in CNC Simulator. Result of testing indicate that carving object have similar form with original object and have appropriate dimension. Integration with the camera allowing the further development online of image to g-code converter and addition 3D reconstruction algorithm so the G-code represents the actual dimension of objects that the camera captured.Key words: Gray scale, G-code, CNC Simulator